Thoraco-abdominal aorta surgical and anesthetic management - Chiesa, Roberto; Melissano, Germano; Zangrillo, Alberto; Coselli, Joseph S.; SpringerLink (Online service). (Milan New York Springer, 2011)
The thoraco-abdominal aortic pathology is not uncommon and represents the ultimate challenge for vascular surgeons. Written by internationally renowned experts in vascular and cardiac surgery, in anesthesiology and in radiology, the volume  deals with the newest endovascular and hybrid approaches, together with more traditional surgical strategies. It is enriched by several figures illustrating the most important diagnostic findings and depicting key techniques and strategies, thus providing a very practical approach to the main problems encountered from diagnosis to postoperative care. Vascular and cardiac surgeons, anesthesiologists, perfusionists and radiologists will find in this volume useful and updated information for the treatment of this very challenging condition.
Section I General Principles 1 Historical Overview. 2 Definitions and Classifications. 3 Epidemiology and Natural History of Thoraco-Abdominal Aortic Aneurysms. 4 Peculiarities and Natural History of Type B Aortic Dissection. 5 Pathology of the Thoraco-Abdominal Aorta. 6 Pathophysiology of Aortic Cross-clamping. 7 Clinical Presentation and Evidence-based Indications to Treatment -- Section II Imaging 8 Diagnostic Imaging of the Aortic Arch and Thoraco-Abdominal Aorta. 9 Magnetic Resonance Imaging of the Aorta. 10 Transesophageal Echocardiography of the Aorta. 11 Preoperative Planning and Sizing for Aortic Endovascular Procedures. 12 Assessment of the Spinal Cord Vasculature with Computed Tomography. 13 Assessment of the Spinal Cord Vasculature with Magnetic Resonance Angiography. 14 Role of Cardiac CT in Assessment of Patients with Thoraco-Abdominal Aortic Aneurysm -- Section III Anesthetic Management 15 Preoperative Care of Patients with Thoraco-Abdominal Aortic Aneurysms. 16 Cardiovascular Evaluation, Risk Stratification, and Management of Postoperative Myocardial Infarction. 17 Perioperative Pharmacological Cardiac Protection. 18 Prevention and Treatment of Renal Insufficiency . 19 Prevention and Treatment of Respiratory Insufficiency. 20 Anesthetic Management of Open Thoraco-Abdominal Aortic Procedures, The Texas Heart Institute Experience. 21 Anesthetic Management of Thoraco-Abdominal Open Procedures. The Mount Sinai Experience. 22 Perioperative Cardiac Monitoring with Transesophageal Echocardiography. 23 Hemostasis, Bleeding, Blood-sparing Strategies, and Allogeneic Transfusions in Thoraco-Abdominal Aortic Aneurysm Surgery. 24 Left Heart Bypass. 25 Management of Postoperative Complications -- Section IV Treatment Strategies and Techniques 26 Surgical Technique for Extent I, II, and III Thoraco-Abdominal Aortic Aneurysms The Texas Heart Institute Experience. 27 Surgical Technique for Extent I, II, and III Thoraco-Abdominal Aortic Aneurysms, The San Raffaele Experience. 28 Surgical Technique for Extent IV Thoraco-Abdominal Aortic Aneurysms. 29 Surgical Replacement of the Entire Aorta. 30 The Frozen Elephant Trunk Technique. 31 Deep Hypothermic Circulatory Arrest for Thoracic Aneurysmectomy through the Left Chest. 32 Neurological Monitoring with Evoked Potentials. 33 Spinal Cord Ischemia. 34 Endovascular Treatment of Thoraco-Abdominal Aortic Aneurysm with Branched Endografts The Nurnberg-Cleveland Experience. 35 Endovascular Treatment of Thoraco-Abdominal Aortic Aneurysm with Branched Endograft The Perugia-Rome Experience. 36 Hybrid Procedures for Thoraco-Abdominal Aortic Aneurysm The London Experience. 37 Hybrid Procedures for Thoraco-Abdominal Aortic Aneurysm The San Raffaele Experience -- Section V Specific Problems 38 Endovascular Treatment of Type B Dissections. 39 The Sandwich Technique for Type B Dissection. 40 Specific Surgical Problems in Marfan Patients. 41 Open Treatment for Aortic Trauma. 42 Endovascular Treatment of Aortic Isthmic Rupture. 43 Redo Open and Endovascular Procedures after Open Thoraco-Abdominal Aortic Aneurysm Repair. 44 Endovascular or Open Treatment of Aortic Coarctation (Typical and Atypical) . 45 Intramural Hematoma and Penetrating Aortic Ulcers. 46 Aortoesophageal and Aortobronchial Fistulas. 47 Anomalies and Variant Anatomy of the Aorta and the Supra-aortic Vessels, Additional Challenges Met by Hybrid Procedures. 48 Quality of Life after Thoraco-Abdominal Aortic Aneurysm Repair. 49 Relative Risk of Paraplegia between Open, Hybrid, and Endovascular Procedures. 50 Statistical Analysis of Operative Results. 51 Communication with the Patient: Ethical Decisions. 52 Postoperative Rehabilitation. 53 Psychological Approach to the Aneurysm Patient -- Section VI Advances in Prosthetic Management 54 Advances in Vascular Graft for Thoraco-Abdominal Aortic Open Surgery. 55 Hybrid Procedures with Dedicated Grafts for Extensive Aortic Aneurysms. 56 The Cook Zenith Devices. 57 The Bolton Relay Devices. 58 The Jotec Devices. 59 The Medtronic Devices Valiant Stent-graft. 60 The Gore TAG Devices. 61 Prophylactic Use of Silver-acetate-coated Polyester Dacron Graft in Aortic Disease for Prevention of Graft Infection. 62 Hemostatic and Structural Adjuncts.
Electronic reproduction.
Keywords: Aorta -- Surgery; Aorta -- Wounds and injuries -- Treatment; Anesthesiology; Electronic books